EMPLOYEE’S PERFORMANCE IS REVIEWED FROM ORGANIZATIONAL CULTURE, MOTIVATION AND WORKLOAD OF THE SUKOHARJO DISTRICT NATIONAL LAND AGENCY OFFICE - Desi Setyaningrum; Eny Kustiyah; Ratna Damayanti; Sri Hartono (ITB AAS Indonesia Surakarta, 2024)
This research aim to identify how Organizational Culture, Motivation and Workload gives impact to Employee’s Performance at the Sukoharjo Regency National Land Agency Office. Civil Servants (PNS) at the Sukoharjo Regency National Land Agency Office is used as research’s population with total 70 employees. Researcher used saturated sample technique on research with 70 sample. There are 3 methods being used in this research, such as the classical assumption test, multiple linear regression test, hypothesis test, coefficient of determination test with SPSS 21 program. This research categorized as quantitative descriptive research that used primary data and secondary data obtained by observation, documentation, questionnaires, interviews and literature study. Final results of this research higlights positive and significant impact from Organizational Culture and Motivation variable on Employee’s Performance, while there is a positive and insignificant effect on Workload variable to Employee’s Performance. The coefficient of determination (R2) of all variables has a contribution of 41.4% and the remaining 58.6% is explained by variables outside this research model.